Analysis of Indonesian People's Sentiments About the Side Effects of the COVID-19 Vaccine on Twitter - Fajar Fatur Rachman; Setia Pramana (Journal of Data Science and Its Applications, 2021)
The large number of people who refuse to get vaccines is one of the biggest challenges for the Indonesian government in dealing with the COVID-19 pandemic. Widespread misinformation and hoaxes about COVID-19 vaccines has made the level of public trust decreases. This paper was written to see how the public's opinion on the side effects of the three COVID-19 vaccines that have been spreading in Indonesia, among them are Sinovac, Astra Zeneca and Moderna. There will be a sentiment analysis and grouping of public conversations on Twitter with LDA regarding the side effects of the three vaccines. From the results obtained, it is expected to be a reference for the government or related parties in order to validate the issues that circulated among the society regarding the side effects of the COVID-19 vaccine. From the results of the analysis, it was found that in the Sinovac vaccine type, people tend to state that the side effects felt are quite mild, dominated by the words sleepy, achy & hungry. While for the Astra Zeneca & Moderna vaccine, people tend to state that the side effects are quite severe, such as fever, pain, and dizziness. The results of the analysis also found that the Astra Zeneca vaccine was the type of vaccine that received the most negative opinions from the public.